2016
DOI: 10.3847/0004-637x/830/2/89
|View full text |Cite
|
Sign up to set email alerts
|

RESOLVING THE DISCREPANCY OF GALAXY MERGER FRACTION MEASUREMENTS AT z ∼ 0–3

Abstract: We measure the merger fraction of massive galaxies using the UltraVISTA/COSMOS Ks-band selected catalog, complemented with the deeper, higher resolution 3DHST+CANDELS catalog selected in the HST /WFC3 H -band, presenting the largest mass-complete photometric merger sample up to z ∼ 3. We find that selecting mergers using the H 160 -band flux ratio leads to an increasing merger fraction with redshift, while selecting mergers using the stellar mass ratio causes a diminishing redshift dependence. Defining major a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
193
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(234 citation statements)
references
References 192 publications
(312 reference statements)
40
193
1
Order By: Relevance
“…In Figure 5, we compare our lightcone-based Illustris merger fraction estimates to observational measurements by Man et al (2016). Here we use the same stellar mass (M * > 10 10.8 M ) and separation (10 < d/(kpc/h) < 30) criteria for the simulated points as Man et al (2016) used for the observed ones.…”
Section: Comparison To Datamentioning
confidence: 99%
See 4 more Smart Citations
“…In Figure 5, we compare our lightcone-based Illustris merger fraction estimates to observational measurements by Man et al (2016). Here we use the same stellar mass (M * > 10 10.8 M ) and separation (10 < d/(kpc/h) < 30) criteria for the simulated points as Man et al (2016) used for the observed ones.…”
Section: Comparison To Datamentioning
confidence: 99%
“…At z 1, we find severe cosmic variance owing to the small volume surveyed, and so we cannot make strong conclusions about how these lightconebased pair fractions evolve to z = 0. With larger simulations, we would expect to recover the expected decrease in the merger fraction from z = 1 to z = 0 (e.g., Lotz et al 2011;Man et al 2016). Figure 1 which merge by z = 0.…”
Section: Pair Statistics and Merger Ratesmentioning
confidence: 99%
See 3 more Smart Citations